Literature and the relational self - Schapiro, Barbara A. (Literature and psychoanalysis, 1994)
While psychoanalytic relational perspectives have had a major impact on the clinical world, their value for the field of literary study has yet to be fully recognized. This important book offers a broad overview of relational concepts and theories, and it examines their implications for understanding literary and aesthetic experience. The author reviews feminist applications of relational-model theories, and considers D.W. Winnicott's influential ideas about creativity and symbolic play. The eight incisive essays in this volume apply these concepts to a close reading of various nineteenth- and twentieth-century literary texts: an essay on Wordsworth, for instance, explores the poet's writing on the imagination in light of Winnicott's ideas about transitional phenomena, while an essay on Woolf and Lawrence compares identity issues in their work from the perspective of feminist object relations theories.